Analisis Perkembangan Trading Saham Syariah Periode 2017-2020 - Ika Anda Rini; Elida Elfi Barus; Zulpahmi Lubis (-, 2022)
Sharia stock trading is a transaction of buying and selling sharia shares in the short term with the aim of getting the maximum profit. In this study, the development of sharia stock trading is shown by three sharia stock indices, such as the Sharia Stock Index (ISSI), the Jakarta Islamic Index (JII), and the Jakarta Islamic Index 70 (JII70). The results of this study indicate that the development of Islamic stock trading from 2017 to 2020 can be said to be stable. This is due to the stable Islamic stock index in those years. Although in 2020 the state of the Islamic stock index had decreased due to the impact of the Covid-19 pandemic, the decline was not too significant. The decline occurred in March 2020 when Covid-19 was first announced. Despite being affected by Covid-19, the Islamic stock index was slowly able to rise again in the following months. This shows that Islamic stocks are able to recover themselves in restoring the stability of their market capitalization. Therefore, during the period 2017 to 2020, the Islamic stock index which shows the development of Islamic stock trading can be said to be stable.